The Influence of Digital Diplomacy on Foreign Policy - AZEEZ, Ismail Adaramola Abdul (Journal of Tourism Economics and Policy, 2023)
The Internet revolution has affected all aspects of life, including international relations. Diplomacy as a tool of foreign policy has also being transformed by this revolution. This paper examines the concept of digital diplomacy, focusing on the use of digital media in the field of diplomacy and how countries are utilizing these tools in the pursuit of their foreign policies. It examines the opportunities and challenges these media offer for diplomatic activities, and argues that countries cannot afford to be left behind in this era of digital diplomacy as they can greatly benefit from these emerging diplomatic trends. Digital diplomacy and Internet activities as a whole can greatly assist in projecting a state’s foreign policy positions to domestic and foreign audiences. digital diplomacy helps to strength relations between North and South, it gives several chances in getting authentic information which enhances economic, political and diplomatic relations in an International arena.